Membangun Karakter Konservasi melalui Origami bagi Pembelajar Bahasa Jepang - Lispridona Diner (Anterior Jurnal, 2018)
Character education has an important role in individual development. Every individual who has good character starts early. In Indonesia, character education in recent years has become part of formal education. It starts with character-based PAUD, followed by SD to SMA/MK/MAN which uses a curriculum known as the 2013 curriculum (kurtilas or K13). At universities such as Semarang State University (UNNES) since March 12, 2010 Unnes declared itself to be a Conservation University. As a Conservation University, since then UNNES has a vision of "becoming an international-standard conservation university that is healthy, superior and prosperous in 2020". To support the program, community service is carried out by realizing character education through origami. The method of implementation in this service program is teaching and evaluation. The servant is an observer who observes the process of directing the activities directly to the community from the beginning to the end. On the implementation of the participants were 32 people. Based on the activities that have been carried out it can be concluded that through origami can realize the character of conservation of UNNES which is humanistic, creative and honest by 100%, inspirational, caring, sporty and fair at 80%. While innovative is 70%.